Heat-related issues and practical applications for Paralympic athletes at Tokyo 2020 - Griggs, K. E.; Stephenson, B. T.; Price, M. J.; Goosey-Tolfrey, V. L. (Temperature, 2020)
International sporting competitions, including the Paralympic Games, are increasingly being held in hot and/or humid environmental conditions. Thus, a greater emphasis is being placed on preparing athletes for the potentially challenging environmental conditions of the host cities, such as the upcoming Games in Tokyo in 2020. However, evidence-based practices are limited for the impairment groups that are eligible to compete in Paralympic sport. This review aims to provide an overview of heat-related issues for Paralympic athletes alongside current recommendations to reduce thermal strain and technological advancements in the lead up to the Tokyo 2020 Paralympic Games. When competing in challenging environmental conditions, a number of factors may contribute to an athlete`s predisposition to heightened thermal strain. These include the characteristics of the sport itself (type, intensity, duration, modality, and environmental conditions), the complexity and severity of the impairment and classification of the athlete. For heat vulnerable Paralympic athletes, strategies such as the implementation of cooling methods and heat acclimation can be used to combat the increase in heat strain. At an organizational level, regulations and specific heat policies should be considered for several Paralympic sports. Both the utilization of individual strategies and specific heat health policies should be employed to ensure that Paralympics athletes` health and sporting performance are not negatively affected during the competition in the heat at the Tokyo 2020 Paralympic Games.